The role of the oral microbiota in the causal effect of adjunctive antibiotics on clinical outcomes in stage III-IV periodontitis patients - Kleine Bardenhorst, Sven; Hagenfeld, Daniel; Matern, Johannes; Prior, Karola; Harks, Inga; Eickholz, Peter; Lorenz, Katrin; Kim, Ti-Sun; Kocher, Thomas; Meyle, Jörg; Kaner, Doğan; Jockel-Schneider, Yvonne; et al. (Microbiome, 2024)
Periodontitis, a prevalent chronic inflammatory disease, offers insights into the broader landscape of chronic inflammatory conditions. The progression and treatment outcomes of periodontitis are closely related to the oral microbiota’s composition. Adjunctive systemic Amoxicillin 500 mg and Metronidazole 400 mg, often prescribed thrice daily for 7 days to enhance periodontal therapy’s efficacy, have lasting effects on the oral microbiome. However, the precise mechanism through which the oral microbiome influences clinical outcomes in periodontitis patients remains debated. This investigation explores the pivotal role of the oral microbiome's composition in mediating the outcomes of adjunctive systemic antibiotic treatment.